Plateauing and Its Consequences for Educators and Educational Organizations - Milstein, Mike. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
Plateauing is an individual's conviction that continued progress is impossible. This conviction occurs as a consequence of long periods of occupational stability. When practitioners doubt the probability of promotion or the importance of their work and find their work to be boring and redundant, they are exhibiting symptoms of plateauing rather than those of stress. Structural plateauing occurs when employees cannot obtain promotions. In education, this type of plateauing is due to the dearth of administrative positions available. Content plateauing, by contrast, occurs when employees master their role, believe that little more can be learned about the role, find the work redundant, and become bored. For instance, teaching at the same grade level for 20 or more years is unlikely to provide opportunities for professional growth. The consequences of plateauing may include poor performance, lack of growth, job turnover, excessive absenteeism, decreased productivity, decreased enthusiasm, decreased self-esteem, other morale problems, and a contagious spread of low enthusiasm. Most plateaued employees have been in the same occupational position for over 5 years. Organizations may help to remedy plateauing by developing career transitions, reducing the emphasis on promotion as the symbol of success, and providing supportive supervision. Individuals may accept plateauing and look for satisfaction somewhere else, or they may seek lateral occupational changes or seek a similar position in a different organization. Further research is necessary to more thoroughly examine the phenomena. Thirty-six references are included. (RG)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (New Orleans, LA, April 5-9, 1988).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Ladders; Elementary Secondary Education; Emotional Response; Employee Attitudes; Job Satisfaction; Morale; Motivation; Occupational Mobility; Professional Development; Promotion (Occupational); Research Needs; Work Attitudes; Speeches/Meeting Papers; Information Analyses